Chemical properties analysis of soygurt with ginger (Zingiber officinale var.roscoe) extract as functional foods. Issue 1 (April 2021) - Anggraini, A A; Devi, M; Nurjanah, N; Sunaryo, N A
Abstract: The processing of soy milk into soygurt was an effort to eliminated the soybean flavor. Several studies showed that plain soygurt still had soybean flavor. The addition of (Zingiber officinale var. Roscoe) extract was an alternative to eliminate the distinctive soybean flavor. This experiment aimed to study the chemical properties of soygurt, which consist of protein, fat, ash, lactic acid, pH. This research used a completely randomized design with one factor of ginger extract concentration (i.e. 4%, 5% and 6%) and all treatments were carried out in duplicate. The collected data were analyzed by One Way ANOVA. If the result was significant (< 0.05), it would be processed by the DMRT test. The results showed the levels of chemical properties of soygurt were 4.507-4.987% of protein; 2.859%-3.220% of fat 0.455-0.56% of ash, 1.710-2.068% of lactic acid and 3.965-4.230 pH value. The experimental results showed that the addition of ginger extract was also proven to significantly affect the chemical properties of soygurt. The addition of ginger (Zingiber officinale var. Roscoe) extract could increase the levels of protein, ash, lactic acid and could reduce fat levels and pH value.